THE EFFECTS OF CARRYING THE M-SHAPE METHOD ON BONDING ATTACHMENT AND INFANT'S SLEEP QUALITY - Brivian Florentis Yustanta (Midwifery Department, UNS (Universitas Sebelas Maret) Surakarta, 2023)
Background: Carrying an infant using M-shape method is vital in creating a bond of affection (bonding attachment) between mother and infant. Carrying using the M-shape method makes the infant calmer and sleeps easier, because the face of infant facing the person carrying them Objective: The aim of the study was to determine the effect of carrying the M-shape method on bonding attachment and infant's sleep quality. Methods: This research was analytic correlational design with cross sectional approach. It was conducted in Pare Kediri, East Java, Indonesia on June, 9th to 25th 2022. The sampling technique used simple random sampling. The population were all infants 6 to 12 month amount 94 and the sample size were 72 infants. The research data used primary data through interviews. The independent variable was carrying the M-shape method, while the dependent variable were bonding attachment and infant's sleep quality. The research instrument were questionnaires. The data was analyze by Wilcoxon Sign Ranked Test. Result: The result showed that 58,3% were 10-12 months old, 70,8% were the youngest child in their family, (52,8%) had carrying duration for more than an hour a day, and 68,1% were carried most dominantly by their parents. P-value were 0.000 and 0.002 , meaning that there were effects of carrying the M-shape method on bonding attachment and the infant's sleep quality. Conclusion: Carrying with M-shape was an alternative in avoiding the wrong position when carrying and can be done from the beginning of newborn.